EPISTEMOLOGY OF PROSODY IN THE RULES OF RHYTHM - Mohammad Shaker Juma Bakri; Dr. Ahmed Abdylazeez Awaad (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
This research studies propositional rules as an epistemological study, as it takes upon itself the search for the rules laid down by prosody scholars among the folds of books, and explores those rules by conducting a cognitive study, because propositional science is devoid of a comprehensive cognitive study that classifies rules in it similar to other sciences such as jurisprudence. And language, and this study deals with grammar as major and minor, and the major rule in this study is memorizing rhythm, and minor rules branch out from it that goes back to the major in its mission and release of episodic judgments.